Alternatif dan Mekanisme Pengobatan Penyakit yang Disebabkan Topeule pada Etnis Kaili Rai di Desa Silanga - Hendra, Hendra; Helnanur, Helnanur (KAMBOTI: Jurnal Sosial dan Humaniora, 2020)
The method of medication develops following the world of thought and culture of humans. The beliefs in the nonmaterial world have profoundly affected in the early days of traditional medication methods. The period of modern medicine eliminates this belief and offers a more logical understanding of health. The traditional healing methods are not completely lost in these modern times. Its existence can still be found amid rural communities whose minds are reconstructed and isolated by traditional beliefs. The thoughts about health and diseases which come from witchcraft then become a benchmark for them to choose witchery medicine too, which in this case known as dukun. This is then becoming a big problem for the citizens in Silanga Village, where as a result of the belief in black magic possessed by humans to hurt other humans, which in the Kaili Rai Ethnic Language they call the topeule. Those then became the origin of the people to choose dukun (sando) for their medication process. The results of this study indicate that supernatural medical practices are still alive in the midst of the Silanga Village community and are trusted by the community who use them.